SPIRITUALITY, ART AND HEALTH WITHIN THE HOSPITAL CONTEXT: report of an experience with the clowns of joy (Citizenship in Action: Extension and Culture Magazine, 2025)
The extension project “The awakening of health through art - Spirituality, health and art” - (Plantão da joy) emerged with the aim of bringing comfort and lightness from art to hospitalized adults and children, as well as to their families and staff. hospital. The games and the presence of clowns help children to feel included and to deal better with the hospital environment. On the other hand, for adults, the hospital reality can be frightening, representing the loss of routine and submission to a new set of rules. During visits to the Hospital Santa Casa de Misericórdia de Catalão, the academics, dressed as clowns, developed playful activities, such as painting, music and games, with the aim of listening to and relaxing the patients and their companions. The proposal, primarily, listen and then speak, in order to offer a moment for patients to express their feelings and emotions. Two visits in particular stood out. In one of them, a seven-year-old boy expressed his faith and religious knowledge in a surprising way, demonstrating confidence and hope in his recovery. On another occasion, a 14-year-old teenager was diagnosed with Type 1 Diabetes Mellitus, leading her mother to open up about her thoughts and challenges related to her daughter's illness. Studies have shown that playful activities in a hospital environment bring several benefits, such as improved mood, social interaction, acceptance of medical procedures and a more positive emotional state. Spirituality/religiosity has also been associated with better general well-being and lower rates of depression and anxiety, highlighting the importance of holistic approaches to health. The presence of the “joy duty” project contributed to the humanization of the hospital environment, providing moments of lightness and relaxation in the midst of adversity. The ability to communicate and understand between those involved is essential to establish a relationship of trust and complicity, creating a safe environment for dialogue. Finally, the experience report highlights the importance of welcoming and active listening in the hospital context, highlighting the role of the project in promoting well-being and emotional resilience for patients, family members and companions.
Keywords: Clowns; Hospital; Spirituality; Religiosity; Vent